DisProt: intrinsic protein disorder annotation in 2020. Issue Volume 48:Issue D1(2020) (12th November 2019) - Hatos, András; Hajdu-Soltész, Borbála; Monzon, Alexander M; Palopoli, Nicolas; Álvarez, Lucía; Aykac-Fas, Burcu; Bassot, Claudio; Benítez, Guillermo I; Bevilacqua, Martina; Chasapi, Anastasia; Chemes, Lucia; Davey, Norman E; et al.
Abstract: The Database of Protein Disorder (DisProt, URL: https://disprot.org ) provides manually curated annotations of intrinsically disordered proteins from the literature. Here we report recent developments with DisProt (version 8), including the doubling of protein entries, a new disorder ontology, improvements of the annotation format and a completely new website. The website includes a redesigned graphical interface, a better search engine, a clearer API for programmatic access and a new annotation interface that integrates text mining technologies. The new entry format provides a greater flexibility, simplifies maintenance and allows the capture of more information from the literature. The new disorder ontology has been formalized and made interoperable by adopting the OWL format, as well as its structure and term definitions have been improved. The new annotation interface has made the curation process faster and more effective. We recently showed that new DisProt annotations can be effectively used to train and validate disorder predictors. We believe the growth of DisProt will accelerate, contributing to the improvement of function and disorder predictors and therefore to illuminate the 'dark' proteome.